Smart Fermentation Technologies: Microbial Process Control in Traditional Fermented Foods - Chong Shin Yee; Nur Asyiqin Zahia-Azizan; Muhamad Hafiz Abd Rahim; Nurul Aqilah Mohd Zaini; Raja Balqis Raja-Razali; Muhammad Ameer Ushidee-Radzi; Zul Ilham; Wan Abd Al Qadr Imad Wan-Mohtar (Fermentation, 2025)
Traditional fermented foods are appreciated worldwide for their cultural significance and health-promoting properties. However, traditional fermentation production suffers from many obstacles such as microbial variability, varying quality, and lack of scalability. The implementation of smart fermentation technologies, including biosensors, the Internet of Things (IoT), artificial intelligence (AI), and machine learning (ML), hold the key to the optimization of microbial process control, enhance product consistency, and improve production efficiency. This review summarizes modern developments in real-time microbial monitoring, IoT, AI, and ML tailored to traditional fermented foods. Despite significant technical advancements, challenges related to high costs, the absence of standardized frameworks, and access restrictions for small producers remain substantial limitations. This review proposed a future direction prioritizing modular, scalable solutions, open-source innovation, and environmental sustainability. In alignment with Sustainable Development Goal 9 (Industry, Innovation, and Infrastructure), smart fermentation technologies advance sustainable industry through innovation and serve as a critical bridge between traditional craftsmanship and Industry 4.0, fostering inclusive development while preserving microbial biodiversity and cultural heritage.